METODE PENGEMBANGAN MORAL DAN DISIPLIN BAGI ANAK USIA DINI (Martabat: Jurnal Perempuan dan Anak, 2018)
Early childhood development is classified in rapid development, including physical, cognitive, emotional, social, and moral development. Moral is the derivation of the Latin word plural of "Mores", which can be translated manners or customs. Parents and teachers are always thinking of exactly how to apply discipline to children from their toddlers to childhood and to their teens. The purpose of discipline is to direct children to learn about good things that are a preparation for adulthood, as they rely heavily on self-discipline. Hopefully, someday their self-discipline will make them happy, successful and loving. The pleasure of seeing the child's success and the disappointment of seeing their bad attitude is the most effective tool in applying discipline to children. Keywords: moral, discipline, early childhood